1998
DOI: 10.2169/internalmedicine.37.484
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Mastocytosis with Extensive Polypoid Lesions in the Intestines; Successful Treatment with Interferon-.ALPHA..

Abstract: A 35-year-old female presented in 1989 with hepatosplenomegaly, but no conclusive diagnosis was established. From 1992, she experienced transient episodes of facial flushing and palpitations. Osteosclerotic change was detected radiologically. Colonoscopy revealed massive polypoid lesions. Mast cells were demonstrated in bone marrow smear and imprinted preparations of colon biopsy specimens by toluidine blue staining. Plasmaconcentrations of histamine and soluble c-kit were elevated. She was successfully treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 11 publications
(4 reference statements)
0
29
0
Order By: Relevance
“…In many cases, symptomatic measures are employed first but generally are not successful. Ex vivo studies revealed that IFN could exert inhibitory effects on factor-dependent growth of mast cells from circulating progenitor cells in patients with SM and a number of clinical reports have shown IFN to be useful in the treatment of ASM [3,[7][8][9][10][11][12][21][22][23][24][25]. In the largest series of patients reported, Casassus et al treated 20 consecutive adult SM patients with IFN 1-5 MU/m 2 /day SQ, with progressive dose intensification over the first month of treatment, to a maximum of 6 months [26].…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, symptomatic measures are employed first but generally are not successful. Ex vivo studies revealed that IFN could exert inhibitory effects on factor-dependent growth of mast cells from circulating progenitor cells in patients with SM and a number of clinical reports have shown IFN to be useful in the treatment of ASM [3,[7][8][9][10][11][12][21][22][23][24][25]. In the largest series of patients reported, Casassus et al treated 20 consecutive adult SM patients with IFN 1-5 MU/m 2 /day SQ, with progressive dose intensification over the first month of treatment, to a maximum of 6 months [26].…”
Section: Discussionmentioning
confidence: 99%
“…IFN-a is often considered the first-line cytoreductive therapy in symptomatic SM; since the initial report in 1992 [79], several case reports or small series have shown IFN-a (IFN-a2b in most instances) to improve symptoms of MC degranulation, decrease BM MC infiltration, and ameliorate mastocytosis-related ascites/hepatosplenomegaly, cytopenias, skin findings, and osteoporosis [80][81][82][83][84][85][86][87][88][89][90][91][92]. IFN-a treatment is not uniformly effective [93], and the frequency of major response (i.e., complete resolution of one or more baseline 'C' findings) is 20-30%; the optimal dose and duration of IFN-a therapy for SM remain unclear, however concurrent administration of corticosteroids (prednisone) may improve its efficacy (up to 40% major response rate) and tolerability [87,94].…”
Section: Interferon (Ifn)-amentioning
confidence: 99%
“…25,[30][31][32][33][34] Systemic mast cell disorders in humans have been treated with interferon-␣, although the effectiveness of this therapy has been variable. [35][36][37][38][39][40][41][42][43] Recent studies suggest that tumors expressing activating mutations in Kit may be amenable to treatment with Kit inhibitors. This has been particularly relevant for gastrointestinal stromal tumors (GISTs), most of which have deletions of various size in exon 11 of c-kit that lead to autophosphorylation of Kit in the absence of ligand binding.…”
mentioning
confidence: 99%